Evaluation of minimum inhibitory and minimum bactericidal concentration of nano-silver base inorganic anti-microbial agent (Novaron® ) against streptococcus mutans - Goda Holla; Ramakrishna Yeluri; Autar Krishen Munshi (Wolters Kluwer Medknow Publications, 2012)
Objective: We attempted to find the possibility of determining the minimum inhibitory concentration and minimum bactericidal concentration needed for nano-silver base inorganic anti-microbial agent (Novaron® AG 300, AG 1100) against Streptococcus mutans in vitro using broth dilution assay. Materials and Methods: An ampoule of freeze-dried S. mutans NCTC reference strain was revived, and the colony-forming units (CFU) were calculated. The MIC and MBC was determined by broth dilution assay using different concentrations of Novaron® AG 300 and Novaron® AG 1100 against 1 x 10 5 CFU/ml of S. mutans. Results: The MIC and MBC of Novaron® AG 300 and Novaron® AG 1100 against S. mutans were found to be 40 μg/ml. Conclusions: Novaron® has anti-bacterial effect against S. mutans. Further studies are needed to explore the applicability of these silver-supported anti- microbial agents in clinical dentistry.